Safety Risk Factors of Duck Meat Sold in Bogor City - annisa, rizka fajri; Purnawarman, Trioso; Pisestyani, Herwin (Jurnal Sain Veteriner, 2025)
With the increasing demand for duck meat in Bogor City, this poses a risk of the presence of pathogenic bacteria throughout the food supply chain. Traditional markets are one of the places that have a high risk of contamination with pathogenic bacteria that can endanger public health. This study aims to determine the presence of Salmonella and E. coli in duck meat sold in traditional markets in Bogor City and the risk factors that influence the presence of these pathogenic bacteria. This study was a cross sectional study with a total of 45 duck meat samples obtained from 3 traditional markets in Bogor City. Samples were taken to the SKHB IPB Veterinary Public Health Laboratory for microbiological testing. Risk factors that may affect the safety of duck meat were assessed using a questionnaire. The results showed that 13 samples (29%) were positive for Salmonella and 27 samples (60%) were positive for E. coli. The presence of Salmonella and E. coli in duck meat indicates cross-contamination during slaughter, evisceration and poor sanitation and hygiene practices. Continuous monitoring and reporting of the presence of Salmonella and E. coli is needed so that duck meat consumed by the public is safe for consumption.